PEMIKIRAN K.H. AHMAD DAHLAN TENTANG PENDIDIKAN ISLAM - Indah Arlini; Acep Mulyadi (Turats, 2021)
Speak Islamic education means discussing human problems themselves as God’s creatureswho are prepared to be His caliph on earth in order to serve Him. One of the challenges of Islamiceducation is the dichotomy of science. To improve the educational conditions of Muslims in Indonesia,especially Muslims, one of the reformers, KH Ahmad Dahlan, offered a new education system bycollaborating religious and general sciences. According to him, only through education like this, thecondition of Muslims in Indonesia can develop better economically-educationally and educationaleconomically.Based on this context, it can be taken a formulation of the problem related to KH AhmadDahlan’s thoughts on Islamic Education and the relevance of KH’s thoughts. This research is includedin the type of Library Research which is descriptive analysis. In collecting data, the author uses themethod of documentation. In data analysis, the writer uses descriptive analysis technique, by findingcertain patterns, themes, looking for logical relationships between these thoughts, then classifyingthe thoughts of the characters, then finally formulating results to achieve specific generalizations ofideas.The results show that Islamic education according to KH Ahmad Dahlan is an effort to improveliving standards, freedom of creativity, moral goodness, and responsibility for the good of his life,society and the world of humanity, as well as the belief in monotheism. There are five key conceptsto understand KH Ahmad Dahlan’s educational thinking, namely pragmatic, progressive, socialpedagogical,renewal (tajdid), and progressive. The concept of education initiated by Ahmad Dahlanis the concept of integrative Islamic education, namely the integration between religious knowledgeand general science. So that the educational ideals initiated by Ahmad Dahlan are the birth of newhumans who are able to appear as “ulama-intellect” or “scholar-intellect”, namely a Muslim whohas broad knowledge, strong physically and spiritually. The thoughts of KH Ahmad Dahlan are stillrelevant and have an influence that can still be applied to Islamic education in this modern era. In therenewal of Islamic education, it must develop and implement contextualization of existing educationalconcepts, by developing them in accordance with the progress of the times and existing technology.